Adjunctive Use of Circulating Tumor DNA Testing in Detecting Pancreas Cancer Recurrence - Soyano, Aixa E.; Baldeo, Candice; Kasi, Pashtoon M. (Frontiers in Oncology, 2019)
Liquid biopsies (circulating tumor DNA – ctDNA testing) are increasingly being utilized in clinical trials as well as practice for the detection of cancer, monitoring of tumor genomic abnormalities, response to treatment and early detection of relapse/recurrence. Here, we present a challenging case where liquid biopsy was used to confirm an early recurrence of pancreatic cancer where acquisition of tissue was not safe or feasible.